2022
DOI: 10.3389/fgene.2022.832060
|View full text |Cite
|
Sign up to set email alerts
|

Survival Nomogram for Metastasis Colon Cancer Patients Based on SEER Database

Abstract: Introduction: A prediction model for the 1-, 3-, and 5-year survival rates of metastatic colon cancer (mCC) patients was developed by analyzing important risk factors for the prognosis of mCC patients based on the SEER database.Method: The characteristic of 10,946 patients diagnosed with mCC between 2010 and 2015 was obtained from the SEER database. The population was randomly divided into a training cohort and an internal validation cohort in a 7:3 ratio. Univariate and multivariate cox for independent predic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 28 publications
(41 reference statements)
2
7
0
Order By: Relevance
“…Donnelly et al ( 24 ) used univariate and multivariable analyses and found that old age, being unmarried, and living alone formed the independent risk factors of CRC in the United Kingdom. Moreover, Tai et al utilized Cox analysis and found that eight factors including age, grade, surgery, and primary site were significant prognostic factors of mCRC ( 20 ), which is consistent with our research. However, compared with previous studies, our study has some distinct advantages.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Donnelly et al ( 24 ) used univariate and multivariable analyses and found that old age, being unmarried, and living alone formed the independent risk factors of CRC in the United Kingdom. Moreover, Tai et al utilized Cox analysis and found that eight factors including age, grade, surgery, and primary site were significant prognostic factors of mCRC ( 20 ), which is consistent with our research. However, compared with previous studies, our study has some distinct advantages.…”
Section: Discussionsupporting
confidence: 91%
“…mCRC in more than 65% of patients recur after surgical treatment ( 19 ). The long-term survival of patients with mCRC has attracted wide public attention; however, studies focusing on early death in patients with mCRC are rare and should be conducted ( 20 , 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…Over the last decade, the median overall survival for patients diagnosed with mCRC has doubled (26). Regarding treatment options, fluoropyrimidines alone or combined with oxaliplatin or irinotecan became a standard regimen choice.…”
Section: Colorectal Cancermentioning
confidence: 99%
“…In previous studies, we constructed a clinical prediction model based on the clinical data of metastatic colon cancer patients extracted from the SEER database. The nomogram developed with high prognosis prediction accuracy to evaluate the 1-, 3-, and 5-year survival of metastatic colon cancer patients, which will help clinical decision-making of metastatic colon cancer patients after surgery and individualized treatment [ 15 ].…”
Section: Introductionmentioning
confidence: 99%